Association of dry matter intake and energy balance prepartum and postpartum with health disorders postpartum: Part I. Calving disorders and metritis - Pérez-Báez, J.; Risco, C.A.; Chebel, R.C.; Gomes, G.C.; Greco, L.F.; Tao, S.; Thompson, I.M.; do Amaral, B.C.; Zenobi, M.G.; Martinez, N.; Staples, C.R.; Dahl, G.E.; et al. (Journal of dairy science, 2019)
The main objective of this study was to determine the association of dry matter intake as percentage of body weight (DMI%BW) and energy balance (EB) prepartum (−21 d relative to parturition) and postpartum (28 d) with calving disorders (CDZ; dystocia, twins, and stillbirths; n = 101) and metritis (n = 114). For this, DMI%BW and EB were the independent variables and CDZ and metritis were the dependent variables. A secondary objective was to evaluate prepartum DMI%BW and EB as predictors of CDZ and metritis. For this, CDZ and metritis were the independent variables and DMI%BW and EB were the dependent variables. Data from 476 cows from 9 experiments were compiled. Cows that developed CDZ had lesser postpartum DMI%BW from d 3 to 12 and lesser energy-corrected milk (ECM) than cows that did not develop CDZ. Dry matter intake as percentage of BW and EB prepartum did not affect the odds of CDZ. Cows with metritis had lesser prepartum DMI%BW and EB. Each 0.1-percentage point decrease in the average DMI%BW and each 1-Mcal decrease in the average EB in the last 3 d prepartum increased the odds of having metritis by 8%. The average DMI%BW and EB during the last 3 d prepartum produced significant cut-offs to predict metritis postpartum, which were ≤1.6%/d and ≤2.5 Mcal/d, respectively. Cows that developed metritis had lesser overall postpartum DMI%BW and ECM and lesser EB from d 2 to 5 and from d 7 to 11 than cows that did not develop metritis. The main limitation in this study is that the time-order of disease relative to DMI%BW and ECM is inconsistent such that postpartum outcomes were measured before and after disease, which was diagnosed at variable intervals after calving. In summary, prepartum DMI%BW and EB were associated with and were predictors of metritis although the effect sizes were small for metritis, and calving disorders and metritis were associated with decreased DMI%BW and ECM postpartum.